Depressive and anxiety symptoms during the COVID-19 pandemic in the oldest-old population and the role of psychosocial factors: a multivariate and multi-wave analysis - Gerhards, Sina K.; Pabst, Alexander; Luppa, Melanie; Riedel-Heller, Steffi G. (Frontiers in Public Health, 2023)
Background Since the oldest-old population was identified as a high-risk group for a severe course of the coronavirus disease and higher mortality, it was assumed that they might be particularly psychologically burdened. The aim of the study is to analyze the development of anxiety and depressive symptoms over the course of the pandemic from 2020 to 2022, as well as psychosocial factors associated with these outcomes. Method We analyzed data of n = 135 participants aged 78 to 97 years old (2020: M = 86.77, SD = 4.54) with three points of measurement from May to June 2020 (t1), March to May 2021 (t2) and November to January 2022 (t3). Besides sociodemographic variables, worries about the Sars-Cov-2 virus, living situation, perceived social support (ESSI), resilience (BRS), anxiety and depressive symptoms (BSI-18) were assessed. We calculated multilevel mixed-effects generalized linear models with a negative binominal distribution to model anxiety and depressive symptoms over time. Results While there is an increase in depressive and anxiety symptoms in the investigated oldest-old individuals in Germany from 2020 to 2021, there is no further increase in symptomatology from 2021 to 2022. Participants of older age reported higher levels of anxiety symptoms. Higher perceived social support was associated with both less depressive and less anxiety symptoms, while resilience was associated with less depressive symptoms only. More worries about the Sars-Cov-2 virus were associated with higher anxiety levels. Conclusion Overall, the oldest-old population appeared to show rather stable mental health after a slight increase in symptomatology within the first year of the pandemic. Social support is an important factor to target in mental health prevention programs for oldest-old individuals in times of future crises such as a pandemic.